Equivalence assessment of quantitative tannins determination methods, used for analysis of herbal drugs - N. P. Antonova; A. M. Kalinin; S. S. Prohvatilova; E. P. Shefer; T. E. Matveenkova (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article describes results of comparative evaluation of two pharmacopoeial methods used for quantitative determination of tannins in herbal drugs: the titrimetric method of the State Pharmacopoeia of the USSR (XIth edition) that is described in the draft general monograph «Determination of tannins in herbal drugs» to be included in the State Pharmacopoeia of the Russian Federation, XIII edition, and the spectrophotometric method of the European Pharmacopoeia. Basic metrological characteristics of the methods were determined using oak bark as sample herbal drug. Both methods were used to test the quality of 9 herbal drug samples in which tannins were present as the main group of biologically active substances. It was revealed that the determined amount of tannins depends on the method used; and content limits are different for the two methods. Experiments were undertaken with the addition of pyrogallol. A modification of the titrimetric method of the State Pharmacopoeia of the USSR (XIth edition) was considered with a view of increasing tannins yield from herbal drugs; conclusions were made regarding the need to change the tannins limit for the modified method.